Are strong opioids equally effective and safe in the treatment of chronic cancer pain? A multicenter randomized phase IV 'real life' trial on the variability of response to opioids. (2nd March 2016) - Corli, O.; Floriani, I.; Roberto, A.; Montanari, M.; Galli, F.; Greco, M. T.; Caraceni, A.; Kaasa, S.; Dragani, T. A.; Azzarello, G.; Luzzani, M.; Cavanna, L.; et al.
Abstract : This paper shows the results of the study CERP comparing efficacy and safety of four strong opioids in the treatment of cancer pain. We observed similar relief of pain with many differences in therapeutic schedules to achieve and maintain the analgesic effect over time. Moreover, a remarkable number of patients were non/poor responders. Abstract: Background: Guidelines tend to consider morphine and morphine-like opioids comparable and interchangeable in the treatment of chronic cancer pain, but individual responses can vary. This study compared the analgesic efficacy, changes of therapy and safety profile over time of four strong opioids given for cancer pain. Patient and methods: In this four-arm multicenter, randomized, comparative, of superiority, phase IV trial, oncological patients with moderate to severe pain requiring WHO step III opioids were randomly assigned to receive oral morphine or oxycodone or transdermal fentanyl or buprenorphine for 28 days. At each visit, pain intensity, modifications of therapy and adverse drug reactions (ADRs) were recorded. The primary efficacy end point was the proportion of nonresponders, meaning patients with worse or unchanged average pain intensity (API) between the first and last visit, measured on a 0–10 numerical rating scale. (NCT01809106). Results: Forty-four centers participated in the trial and recruited 520 patients. Worst pain intensity and API decreased over 4 weeks with no significant differences between drugs. Nonresponders ranged from 11.5% (morphine) to 14.4% (buprenorphine). Appreciable changes were made in the treatment schedules over time. Each group required increases in the daily dose, from 32.7% (morphine) to 121.2% (transdermal fentanyl). Patients requiring adjuvant analgesics ranged from 68.9% (morphine) to 81.6% (oxycodone), switches varied from 22.1% (morphine) to 12% (oxycodone), discontinuation of treatment from 27% ( morphine) to 14.5% (fentanyl). ADRs were similar except for effects on the nervous system, which significantly prevailed with morphine. Conclusion: The main findings were the similarity in pain control, response rates and main adverse reactions among opioids. Changes in therapy schedules were notable over time. A considerable proportion of patients were nonresponders or poor responders. Clinical Trial Registration: NCT01809106 (https://clinicaltrials.gov/ct2/show/NCT01809106?term=cerp&rank=2 ).